The influence of Al content and heat treatment on the microstructure and properties of austenite-ferrite duplex Fe-Mn-Al-C lightweight steels - Rui Bai; Yunfei Du; Yaqin Zhang; Xiuli He (Journal of Alloys and Metallurgical Systems)
Abtract: In this study, the influence of Al content (9 wt% and 12 wt%) on the microstructure evolution, mechanical properties and deformation behavior of austenite-based Fe-Mn-Al-C lightweight steels were investigated. The Steel with 9 % Al content displayed a dual-phase structure with austenite and less than 5 % ferrite, while the Steel with 12 % Al content contained approximately 23 % ferrite and nanoscale κ-carbide precipitates, influenced by the Al content. Following aging treatment at 600 °C, both steels experienced notable microstructural changes. Coarse carbides, B2, D03, and β-Mn precipitates, appeared during the aging, leading to the deterioration of mechanical properties. The aging treatment improved strength but decreased ductility for both steels, with extended aging leading to deterioration attributed to coarse precipitate formation. Both steels demonstrated effective strain hardening behavior. The aging treatment on the steels significantly impacted the fracture morphologies. The investigation of deformation mechanisms reveals distinct behaviors under low strain conditions. The steels demonstrated a unique staggered dislocation structure and exceptional uniform elongation due to decreasing slip plane spacing. The strength was enhanced by interactions among dislocation arrangements within distinct domain boundaries.